Efektifitas Inisiasi Menyusu Dini (IMD) dalam Menurunkan Kejadian Hipotermi pada BBL di RSUD Ngimbang Lamongan Tahun 2021 - Kustini Kustini; Ayu Erisnawati (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Early initiation of breastfeeding affects the body temperature of newborns, because heat loss in infants is four times greater than in adults. This action as a life saver, early initiation of breastfeeding can also save 22 percent of babies who die before the age of one month. The purpose of this study was to determine the effect of early initiation of breastfeeding on changes in body temperature in newborns. The design of this study used a quasi-experimental approach with pretest and posttest approaches. The sampling method is by accidental sampling. Data were collected by means of observation, and analyzed using a computerized Wilcoxon test with a significance level of P-Sign <0.05. The results showed that almost 90% of newborns before early initiation of breastfeeding experienced a decrease in body temperature and after early initiation of breastfeeding only 10% experienced low body temperature. From the results of statistical testing, the results obtained with Z = -4.243 and P value = 0.000. The conclusion of this study is that there is an effect of early initiation of breastfeeding on changes in body temperature of newborns at Ngimbang Lamongan Hospital in 2021. Looking at the results of this study, it is hoped that midwives will continue to provide early initiation of breastfeeding to every newborn to prevent hypothermia.